Potentials of increasing levels of recycled waste plastic on the physical characteristics of concrete - Charles A Ogbu; Abimbola Y Sangodoyin (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2018)
This research focused on the integration of waste plastic into concrete in a bid to restrain water ingress when exposed to water. Polyethylene water sachet (PWS) was the source of waste plastic used. Waste plastic concrete treatments were designed and cast successfully with percentage waste plastic contents of 0, 0.25, 0.50, 0.75 and 1.00. It also involved a constant water/cement ratio of 0.45, a mix design of 1:2:4 and 2% by 342.85kg cement weight of superplasticizer. Twenty cubes, 20 beams and 45 cylindrical specimens were cast for compressive, flexural, split tensile and water absorption tests respectively at 28 days of curing. Waste plastic treatments of 0.5% and 0.75% contents had the highest compressive strength. Water absorption characteristics of waste plastic concrete dropped with increasing plastic waste content to 0.75% after which further increase gave undesirable effects. Optimum water absorption (impermeability) were observed between 0.50% and 0.75% waste plastic content. Waste plastic concrete of 0.75% content with compressive strength and water absorption values of 21.19MPa and 0.22% respectively met the requirements of ASTM C55-11, ASTM C139-11 and CP 102. Waste plastic concrete showed desirable characteristics for potential use in the built environment.